Spermatocytic Seminoma with Sarcomatous Transformation: The First Brazilian Case Report - Daniel Carvalho; Ronielly Bozzi; Aline Coltro; Bruno Reis; José Scheinkman (Journal of Urological Surgery, 2018)

(untitled)
The cases of spermatocytic seminoma with sarcomatoid transformation are rare. When there is sarcomatoid transformation, the tumor takes an aggressive pattern, with high rates of metastasis and a worse prognosis. We present the case of a 42-year-old man with a slow enlargement of the left testicle over more than 18 months, which progressed to a pronounced and painful growth in the last six months. Computed tomography showed a left retroperitoneal mass in the renal area affecting the stomach. Total orchiectomy with partial scrotectomy was performed in the left testicle and the patient was referred to the oncology department for chemotherapy.